ANALISIS FAKTOR PENGHAMBAT MEMBACA PERMULAAN PADA SISWA KELAS 2 SD - Annisa Chairunnisa; Dedi Heryadi; Deni Chandra (Universitas Negeri Medan, 2023)
Abstract: This study aims to describe internal and external factors inhibiting early reading in grade 2 elementary school students. The research method used is descriptive qualitative. The instruments used are observation instruments, interviews, questionnaires, and documentation. Data analysis techniques include data reduction, data display, and conclusions. The research results were obtained from 4 students, 1 student could not read, 2 students stammered in reading and 1 student was categorized as able to read. Based on the inhibiting factors for beginning reading, it was found that 1 student was due to psychological factors, namely memory. 1 student due to psychological factors. While 2 students were due to psychological factors and family factors. Thus the inhibiting factors for beginning reading in grade 2 students in Tasikmalaya district are physiological and psychological, namely the lack of interest and motivation of students in learning to read, family environmental factors, and school environmental factors.Keyword: Beginning Reading, Internal and external factorsAbstrak: Penelitian ini bertujuan untuk mendeskripsikan faktor internal dan eksternal penghambat membaca permulaan pada siswa kelas 2 SD. Metode penelitian yang digunakan yaitu kualitatif deskriptif. Instrumen yang digunakan yaitu instrumen observasi, wawancara, angket dan dokumentasi. Teknik analisis data meliputi reduksi data, display data dan kesimpulan. Hasil penelitian yang diperoleh dari 4 orang siswa terdapat 1 siswa belum bisa membaca, 2 siswa terbata-bata dalam membaca dan 1 siswa dikategorikan bisa membaca. Berdasarkan faktor penghambat membaca permulaan di dapatkan hasil bahwa 1 siswa karena faktor psiologis yaitu daya ingat. 1 siswa di karenakan faktor Psikologis. Sedangkan 2 siswa di karenakan faktor psikologis dan faktor keluarga. Dengan demikian faktor penghambat membaca permulaan pada siswa kelas 2 di kabupaten tasikmalaya adalah faktor fisiologis, psikologis yaitu kurangngnya minat dan motivasi siswa dalam belajar membaca, faktor lingkungan keluarga dan faktor lingkungan sekolah.Kata Kunci: Membaca Permulaan, Faktor Internal dan Faktor Eksternal